Validación de un Inventario de roles de masculinidad hegemónica en varones colombianos (2019)
The object of this study was to evaluate the psychometric properties of an inventory to measure the hegemonic masculinity in men residing in an intermediate city in Colombia. A total of 600 participants aged 18 to 65 years were selected using a non-probabilistic sampling for availability (M = 29, SD = 10.7). An inventory of 30 items that measure the adherence to the roles of hegemonic masculinity modified version MNRI-M was applied. Exploratory Factor Analysis EFA revealed five factors that explain 64% of the common variance. Confirmatory Factor Analysis CFA confirmed very good fit of this penta-factorial model in a reduced version of 17 items S-B χ2 = 343.29, gl = 109, NNFI = 0.97; CFI = 0.98. RMSEA = 0.06 IC95% (0.053, 0.067). Alpha and Omega coefficients obtained to estimate internal consistency were between 0.70 and 0.79. Constructed roles of hegemonic masculinity discriminated adequately according to age, educational level, socioeconomic classification, and occupation. It is concluded that MNRI-M possesses adequate psychometric properties.